Evaluating position evaluation - Society for Personnel Administration (Washington D.C : The Society for Personnel Administration, 1963)
This is a critical analysis and appraisal of position evaluation techniques rather than a panacea for the problems of evaluating positions
osc 04/03/2019
Loans
Keywords: Job analysis